Atypical antipsychotic drugs in the treatment of psychiatric disorders - Rybakowski, Janusz (Przewodnik Lekarza/Guide for GPs, 2011)
Antipsychotic (neuroleptic) drugs were introduced for the treatment of schizophrenia in early 1950s. Atypical antipsychotic drugs (AAD) with specific pharmacological profile, introduced since 1990s had to be efficacious in wider spectrum of schizophrenic symptoms (deficit, affective, cognitive) and to cause less disturbances of extrapyramidal system. Some AAD (clozapine, olanzapine, amisulpride, risperidone) proved more efficacious in schizophrenia compared with typical neuroleptics. It was also shown that AAD have mood-stabilizing properties what results in their increased use in bipolar affective illness. In treatment-resistant depression, AAD have been currently employed for augmentation of antidepressant drugs. Atypical antipsychotic drugs are also used in anxiety disorders, Parkinson’s disease and dementia.